STUDENTS’ USE OF DISCOURSE MARKERS IN ORAL PRESENTATIONS - utami roslina (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2022)
This study is a descriptive qualitative study aims at analyzing the use of discourse markers in student’s oral presentations at English graduate program of Semarang state university in academic year 2015/2016. This study used spoken data discourse markers proposed by Blanpain (2009) for data analysis. The data of the study were collected from the students of the second semester in English graduate program of Semarang state university. The method of analyzing the data was coding, classifying, reducing, calculating, interpreting, and drawing inference. The researcher used method and theoretical triangulation to validate the data.The findings of the study showed that the students used discourse markers signpost in their oral presentation such as, getting started, referring to a previous point, starting or announcing a new point, referring to visuals, giving an example or elaboration, expressing reasons and connections, restating, aside markers, inviting questions, and summarizing. The second was the students used gestures, gaze, and intonation to indicate the trasitions. The last the students used the monothone expressions it because they lack of vocabulary.